Keywords : the new language of capitalism - Leary, Patrick John (Haymarket Books, 2019)
Keywords: The NewLanguage of Capitalismchronicles the rise of a new vocabulary in thetwenty-first century. From Silicon Valley to theWhite House, from kindergarten to college, and from the factory floor to the church pulpit, weare all called to beinnovatorsandentrepreneurs, to becuratorsof an ever-expanding roster ofcompetencies, and to becomeresilient and flexible in the face of the insults and injuries we confront at work. In the midst of increasing inequality, these keywords teach us to thrive by applying the lessons of a competitive marketplace to every sphere of life. What's more, by celebrating thevalues ofgrit, creativity, andpassion at school and at work, they assure us that economic success is nothing less than a moral virtue. Organized alphabetically as alexicon, Keywordsexplores the history and common usage of major terms in the everyday language of capitalism. Because the words in this book have successfully infiltrated everyday lifein the English-speaking world, their meanings often seem self-evident, even benign. Who could be against empowerment, after all' Keywords uncovers the unexpectedhistories of words like innovation, which was oncesynonymous with "false prophecy" before it became the prevailing faith of Silicon Valley. Other words, likebest practices and human capital, arerelatively newcoinages that promise us a kind of freedom within a marketplace extending its reach across the public sector and into our private lives. The new language of capitalism burnishes hierarchy, competition, and exploitation as leadership, collaboration, and sharing, modeling for us the habits of the economically successful person: be visionary, be self-reliant, and never, ever stop working.